Feasibility study of BOF slag containing honeycomb particles in asphalt mixture. (15th October 2016) - Chen, Zongwu; Wu, Shaopeng; Xiao, Yue; Zhao, Meiling; Xie, Jun
Highlights: CHS were used as coarse aggregate and filler, respectively. Honeycomb slag contained in CHS resulted in asphalt absorption. The fracture of honeycomb slag happened during compaction. Honeycomb slag worsened the rutting, crack and moisture resistance. Asphalt mixture with CHS powder showed satisfied performances. Abstract: Some honeycomb particles exist in Basic Oxygen Furnace (BOF) slag. The feasibility of preparing asphalt mixture with BOF slag containing honeycomb particles (CHS) was discussed in this research. The characteristics of raw materials including surface texture, physical phase, chemical composition and technical property were first evaluated. Then the volumetric indexes and performances of asphalt mixtures designed by Marshall procedure were discussed. The scanning electron microscope (SEM) was innovatively used to observe micro cracks of asphalt mixture. Results suggested that honeycomb slag used as coarse aggregate increased the asphalt content, lowered the rutting resistance, crack and moisture resistance of asphalt mixture. Asphalt mixture containing CHS filler showed satisfied performance.